Answer: -5x + 2y=2 Step-by-step explanation: [tex]- 7x + 3y = 2 \\ – 2x + y = 0 \\ subtracting \: this.we \: have \\ ( – 7x \: + 3y – 2) – ( – 2x + y) \\ – 7x + 2x + 3y – y – 2 \\ – 5x + 2y – 2 \\ therefore \: we \: have \\ – 5x + 2y = 2[/tex] Log in to Reply

Answer:-5x + 2y=2

Step-by-step explanation:[tex]- 7x + 3y = 2 \\ – 2x + y = 0 \\ subtracting \: this.we \: have \\ ( – 7x \: + 3y – 2) – ( – 2x + y) \\ – 7x + 2x + 3y – y – 2 \\ – 5x + 2y – 2 \\ therefore \: we \: have \\ – 5x + 2y = 2[/tex]